Purchase of plots of land included in an agricultural holding transferred to the state under the retirement and disability pension regulations - Świderski, Krzysztof (Przegląd Prawa Rolnego, 2020)
The purpose of this article was to resolve problems related to the claims concerning the purchase of land on which the buildings which were once part of an agricultural holding transferred to the State for pension benefits. The solutions adopted by the legislator do not harmonise with the regulations governing the acquisition of land by other social groups. An administrative claim procedure and the absence of time limits for the filing of claims are a shortcoming. The right solution would be to giving farmers and their successors statutory priority in the acquisition of land with buildings. Such priority should be implemented during the sale procedure.